The effect of amphetamine-type stimulants on immune response in HIV-infected individuals: a retrospective cohort study - Li, Tao; Li, Zuoliang; Liu, Hai; Chen, Jinsi; Li, Yanwei; Zhou, Xin; Zhang, Su; Li, Bei; Ren, Yulan (Frontiers in Immunology, 2026)
BackgroundThe co-occurrence of amphetamine-type stimulant (ATS) abuse and HIV infection is prevalent, yet the impact of ATS abuse history on immune reconstitution in people living with HIV (PLWH) remains uncertain. We aim to assess the impact of ATS abuse history on immune reconstitution in PLWH with low CD4+ levels and high ART adherence.MethodsUsing data from China’s National Free Antiretroviral Treatment Program and Drug Rehabilitation Management Platform data, we identified PLWH who met the inclusion criteria between 2016 and 2022. Propensity score matching paired participants. Primary outcomes focused on immune response after 2 years of ART, and secondary outcomes including CD4+ T-cell count recovery, net increase in CD4+ T-cell count, CD4+ T-cell growth rate, time to immune response, and AIDS-related mortality.ResultsAfter matching 2,372 PLWH into ATS and non-ATS cohorts, the ATS group exhibited lower immune response rates, delayed responses, smaller increases in CD4+ T-cell counts, and slower initial CD4+ T-cell growth, although growth rates were comparable at later time points. Cox regression analysis identified ATS exposure as an independent risk factor for poorer immune responses 2 years after ART initiation [HR: 0.558 (0.485-0.643), P<0.001]. Kaplan-Meier analysis demonstrated a lower cumulative immune response rate in the ATS group. Longer ATS exposure was associated with reduced immune response rates in PLWH after ART initiation.ConclusionsA history of ATS abuse hinders HIV immune reconstitution, underscoring the need for tailored services for PLWH with ATS exposure.